2010
DOI: 10.1002/pon.1678
|View full text |Cite
|
Sign up to set email alerts
|

Women with advanced breast cancer and their spouses: diversity of support and psychological distress

Abstract: Objective: The current study examines the effect of perceived support from different agents (spouse, family, friends, religion-spirituality) on psychological distress experienced by women with advanced breast cancer and their male spouses.Methods: In all, 150 couples consisting of women with advanced breast cancer and their spouses completed the Cancer Perceived Agent of Support Questionnaire and the Brief Symptom Inventory Scale.Results: Spouses reported more psychological distress (global, depression and anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
145
2
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(171 citation statements)
references
References 50 publications
11
145
2
13
Order By: Relevance
“…Men delay seeking help or are unwilling to seek help because of masculinity norms, stereotypes, traditional values (Galdas et al, 2005;Addis and Mahalik, 2003). Hasson-Ohayon et al (2010) found that friend is the most important support for the male partner. Getting together male's support group may be benefit strategy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Men delay seeking help or are unwilling to seek help because of masculinity norms, stereotypes, traditional values (Galdas et al, 2005;Addis and Mahalik, 2003). Hasson-Ohayon et al (2010) found that friend is the most important support for the male partner. Getting together male's support group may be benefit strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with the worsening of the patients' physical function and emotions, caregivers also experience fatigue and overload (Gaugler et al, 2005). Being as a caregiver, male spouse of metastatic cancer patients are at high risk of physical and psychological distress (Hasson-Ohayon et al, 2010).…”
Section: Living Experiences Of Male Spouses Of Patients With Metastatmentioning
confidence: 99%
See 1 more Smart Citation
“…This result underscores the need to consider that, for improvement of levels of hope and consequent prospect of future health of patients undergoing chemotherapy, it is important that health professionals pay attention to the "feeling alone" and develop care plans that reduce this feeling. Support networks contribute to coping with cancer, and such support may come from other family members, as well as relations of friendship in the community, (10) including the social, economic and functional and/or emotional spheres.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Yapılan diğer çalışmalarda da benzer olarak bakım veren eşlerin daha yüksek oranda depresyon yaşadığı ve hastanın eşi olmanın bakım verenin depresyonuna katkıda bulunan önemli faktörler-den birisi olduğu belirtilmiştir. [20,28] Çalışmalar da bakım verenlerde kötü sağlık durumu ile yüksek düzeyde depresyon oranlarının ilişkili olduğu vurgulanmaktadır. [10,[29][30][31] Bakımda destek almayan bakım verenlerin depresyon ortalama puanlarının yüksek olduğu tespit edilmiştir (p<0.05) (Tablo 3).…”
Section: Tablounclassified